2008
DOI: 10.1021/jp7106473
|View full text |Cite
|
Sign up to set email alerts
|

Porosity Inherent to Chemically Crosslinked Polymers. Poly(N-vinylimidazole) Hydrogels

Abstract: Swollen polymer networks exhibit multiscale pores filled with solvent. Such porosity, inherent to cross-linked polymers, determines some of their most relevant physical properties and applications. In this research, several samples of chemically crosslinked poly(N-vinylimidazole) were synthesized with the same permanent crosslinking density at two different conversions, and their inherent porosity was characterized on freeze-dried specimens by SEM, TEM and nitrogen physisorption. It was thus found that all of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…3 The porous morphology depends on several variables such as the porogen and crosslinker used in feed, or the previous thermal history of the sample. [3][4][5][6][7][8][9][10][11][12] Sponges and macroporous polymers are prepared with porogen agents 9,10 or other porogenic methods. 4,11,13,14 Polymer networks synthesized without using porogens, exhibit pores (inherent porosity 12 ) that in the swollen state are filled with solvent and contribute significantly to the degree of swelling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The porous morphology depends on several variables such as the porogen and crosslinker used in feed, or the previous thermal history of the sample. [3][4][5][6][7][8][9][10][11][12] Sponges and macroporous polymers are prepared with porogen agents 9,10 or other porogenic methods. 4,11,13,14 Polymer networks synthesized without using porogens, exhibit pores (inherent porosity 12 ) that in the swollen state are filled with solvent and contribute significantly to the degree of swelling.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] Sponges and macroporous polymers are prepared with porogen agents 9,10 or other porogenic methods. 4,11,13,14 Polymer networks synthesized without using porogens, exhibit pores (inherent porosity 12 ) that in the swollen state are filled with solvent and contribute significantly to the degree of swelling. 5,8,11,12 The roles of morphology and crosslinking in determining polymer properties are difficult to be distinguished because upon changing crosslinking, the morphology changes too.…”
Section: Introductionmentioning
confidence: 99%
“…Opacity is frequently considered to be the clearest sign of heterogeneity or inhomogeniety in samples [26]. Furthermore, it has previously been shown that phase separation is a phenomenon commonly occurring in crosslinking polymerization [18,25,26] and that increasing crosslinker content is an inducing factor [21,22].…”
Section: Synthesismentioning
confidence: 99%
“…Furthermore, it has previously been shown that phase separation is a phenomenon commonly occurring in crosslinking polymerization [18,25,26] and that increasing crosslinker content is an inducing factor [21,22]. In the literature it has been suggested that the solubility for PAA gels in Ca 2+ containing solution is reduced [10], and that precipitation of PAA occurs in presence of high Ca 2+ concentration [14].…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation